Tuition Fees and Student Financial Assistance: 2010 Global Year - Marcucci, Pamela; Usher, Alex (International Higher Education, 2011)
In the face of the on-going global financial crisis, higher education budgets are under pressure. As of 2010, tuition fees are not yet rising in most countries, and some countries continue to make steps to make education more affordable. However, on balance, the global trend in 2010 was towards greater cost-sharing (higher tuition, lower student aid), and this trend is expected to accelerate in the coming years.